Using Portfolio Assessment to Improve the Students’ Recount Writing Performance at SMPN.6 Pare pare - Salim, Ramlah (Universitas Terbuka, 2023)
One of the techniques that can be used to improve the students’ recount writing performance is by using portfolio assessment. The objective of the research was to investigate the use of portfolio can improve the students’ recount writing performance at SMPN.6 Parepare. The research applied quasi experimental method with experimental and control group consists of 50 students. The data were collected by giving pre-test and post-test in term of writing test. The data collected were then analyzed by using ANOVA and t-test. The result showed that the students’ score on the post-test were significantly higher than the pre-test. The value of the t-test was greater than t-table. It was that tvalue (4.446) > ttable (1667) and the sig.(2-tailed) value of post test score was lower 0.000 < 0.05. The mean score of the pre-test is 66.76 and the post-test is 84.72. It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It means that the use of portfolio assessment was effective to improve the students’ writing recount text performance